Information Technology Governance Audit on implementing the XYZ Mobile Application Using the COBIT 5 Framework with the BAI Domain - Jeremia Juan Michael; Leonardus Rizky Mahendra; David Ezra Prasetyo; Timotius Hamonangan Lumban Tobing; erick fernando (PT. BERBAGI TEKNOLOGI SEMESTA, 2023)
Information technology is needed in every area of human life, including the company's business needs. In the company's business activities, technology has a very important role. Therefore, information technology governance is needed so that information technology can be utilized optimally. PT XYZ has a sales service application for products with the XYZ label. This study conducted an audit on the XYZ application with the COBIT 5 domain BAI framework to determine the application's maturity level and provide suggestions for future development. The maturity level results in a value of 3,356 with a predetermined process status, and there is still a large enough gap between each subdomain with the results of the average maturity level in the BAI domain. The results of this study are that it can be seen the value of the application maturity level and recommendations for system development that can be carried out.